2006
DOI: 10.1074/jbc.m601775200
|View full text |Cite
|
Sign up to set email alerts
|

Locating the Carboxylate Group of GABA in the Homomeric rho GABAA Receptor Ligand-binding Pocket

Abstract: GABA3 is the major inhibitory neurotransmitter in the mammalian central nervous system (1). It mediates its effects via both ionotropic (GABA A ) and metabotropic (GABA B ) receptors. GABA C receptors are a subfamily of GABA A receptors and are sometimes referred to as GABA receptors, because the first subunit identified from this class of receptor was called 1 (2). These receptors have been separated from "classic" GABA A receptors because of their distinct pharmacological properties;GABA C receptor-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 26 publications
(32 reference statements)
9
56
0
Order By: Relevance
“…32 Mutation of serine 243 to alanine (S243A) afforded mutant receptors that were functional, with GABA potency reduced only by approximately 2-fold compared to ρ 1 wild-type. 32 The lack of a hydroxyl group in the residue at 243 did not strongly change the potency of GABA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Mutation of serine 243 to alanine (S243A) afforded mutant receptors that were functional, with GABA potency reduced only by approximately 2-fold compared to ρ 1 wild-type. 32 The lack of a hydroxyl group in the residue at 243 did not strongly change the potency of GABA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32 Mutation of serine 243 to alanine (S243A) afforded mutant receptors that were functional, with GABA potency reduced only by approximately 2-fold compared to ρ 1 wild-type. 32 The lack of a hydroxyl group in the residue at 243 did not strongly change the potency of GABA. However, our results confirm the fact that removal of the hydroxyl group at T244 was not tolerated, 27 indicating that the T244 has a more important role in ρ 1 receptor GABA mediated channel gating than S243.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This absence of responsiveness is perhaps not surprising, as both GABA and muscimol are zwitterionic at neutral pH, and the charged residue R158 presumably plays an important role in agonist binding and positioning. 39 The findings that removing arginine in the R158A mutant yields a 200-fold increase in EC 50 and that the double mutant R158D-D204R is inactive together suggest that the absence of a positively charged residue specifically at Position 158 strongly diminishes the binding affinity of the GABA and muscimol.…”
Section: Probability Analysis Of Evolutionary Selection Pressurementioning
confidence: 99%
“…Remarkably, experimental data obtained from the literature demonstrated that mutations at positions with the lowest x-values usually had significant effects on the receptor function or expression. [15][16][17]39,40,42 Additionally, we have assessed the advantage of using evolutionary information in improving the quality of the homology model of GABA C receptor. We have compared our model with the model obtained using standard programs with default settings and default search results (as described in ''Methods'').…”
Section: Probability Analysis Of Evolutionary Selection Pressurementioning
confidence: 99%
See 1 more Smart Citation